Women with von Willebrand disease - Scharrer, I. (Hämostaseologie, 2004)
The clinical presentation of VWD shows sex-related differences of symptoms. In women the most typical symptoms are menorrhagia, bleeding during and after delivery or abortion and bleeding in connection with caesarean section or gynaecological surgery. Menorrhagia is one of the most common symptoms presented to gynaecologists. In 7-20% of menorrhagia the underlying cause is VWD, in our cohort of 185 women with menorrhagia the prevalence of VWD was even 32%. On the other hand in women with VWD menorrhagia with onset at the menarche can be found in 60-93%, influencing substantially their morbidity and quality of life. During pregnancy women with mild VWD experience a decrease of bleeding tendency due to an increase of endogenous VWF. But as the VWF concentration drops rapidly after delivery, the post-partum period is often associated with significant bleeding complications. In severe forms of VWD the bleeding risk is high during delivery and postpartum period. Laboratory monitoring and therapeutical measures should be continued for 8-10 days after delivery. During menopause the clinical situation improves for most of the women with mild or moderate VWD.
Keywords: Menorrhagia; delivery; postpartum bleeding